DESIGN OF COMPOSITE GIRDER STRUCTURE BRIDGE OF SELUANG-1 RIVER PT LIFERE AGRO KAPUAS KAPUAS DISTRICT - A. Riski Fauzi; Markawie Markawie (Universitas Lambung Mangkurat, 2019)
The bridge at the Seluang-1 river is located around the palm oil plantation land owned by PT Lifere Agro Kapuas, Kapuas Regency, Central Kalimantan. In this Seluang-1 river, a bridge is planned to be built to facilitate the mobilization of palm oil plantation crops and other matters as well as transportation in the PT Lifere Agro Kapuas area because before there was a bridge the transportation traffic was cut off by the river so it had to circle quite a long way. The bridge is designed as a bridge with composite girder structure type. The methodology in the design of loading uses the SNI 1725-2016 concerning on the Loading Standards for Bridges and SNI 2833-2016 concerning on the Earthquake Resilience Planning Standards for Bridges. For methodology in designing concrete structures refer to SNI 2847-2013 concerning Structural Concrete Requirements for Buildings and methodology in designing steel structures refers to SNI 1729-2015 concerning Specifications for Structural Steel Buildings. The material used for abutment uses reinforced concrete material. The methodology in calculating the bearing capacity of the foundation uses the method by Mayerhof and also the method by Kazuto Nakazawa, while the methodology in calculating the lateral bearing capacity uses the Broms method, with the efficiency of the pile using a graph by O’Neill. From the results of topographic measurements taken a bridge design with a span of 30 m with a total bridge width of 7 m. The slab design is 25 cm thick with the compressive strenght of concrete is fc’ 30 MPa (K-350). The steel girder beam used WF Profile 1350.800.100.130 and the diaphragm beam used WF Profile 250.125.6.9 with BJ55 steel quality (fy 410 MPa). Whereas in the lower structure, the abutment designed with a height of 350 cm, a width of 320 cm and a length of 850 cm, was used with compressive strenght of concrete is fc’ 30 MPa (K-350). In the foundation used Spun Pile type piles with a diameter of 60 cm with a depth of 30 m piling as much as 8 piles on one abutment. Obtained Qallow = 116,37 tons > Qload = 114,69 tons so that the foundation is declared safe. The planned budget for the construction of a bridge on the Seluang-1 river is Rp 8.990.566.000,00.-